2017
DOI: 10.1007/s11010-017-3003-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-192 suppresses cell proliferation and induces apoptosis in human rheumatoid arthritis fibroblast-like synoviocytes by downregulating caveolin 1

Abstract: Fibroblast-like synoviocytes (FLSs) play an important role in the pathogenesis of rheumatoid arthritis (RA). This study was conducted to explore the role of microRNA (miR)-192 in the regulation of the biology of RA-FLSs. The expression of miR-192 in RA and healthy synovial tissues was measured. The effects of overexpression of miR-192 on RA-FLS proliferation and apoptosis were investigated. Luciferase reporter assay and Western blot analysis were performed to identify direct target genes of miR-192. RA synovia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 23 publications
3
30
0
1
Order By: Relevance
“…In line with our results, miR-192 has been reported to inhibit cell proliferation and induce apoptosis in vitro 39,40 and rheumatoid arthritis 41 . Also, p53 can induce miR-192 to promote its activation facilitating cell cycle arrest 42,43 .…”
Section: Discussionsupporting
confidence: 92%
“…In line with our results, miR-192 has been reported to inhibit cell proliferation and induce apoptosis in vitro 39,40 and rheumatoid arthritis 41 . Also, p53 can induce miR-192 to promote its activation facilitating cell cycle arrest 42,43 .…”
Section: Discussionsupporting
confidence: 92%
“…To data, several miRNAs have been mentioned as downstream genes of SIN, including miR-101 (Liu, Man, & Zhao, 2018), miR-324-5p (Song et al, 2015), and miR-155 (Yu et al, 2013). miR-192 has been mentioned as a differentially expressed miRNA in rheumatoid arthritis synovial tissues, and its expression is associated with fibroblast-like synoviocytes growth (Li, Jin, & Lu, 2017). miR-192 expression is sensitivity to LPS stimulation (Zhang et al, 2015), and the physiological role of miR-192 in inflammatory system has been reported (Chu & Xu, 2016 et al (2015), which confirmed our hypothesis.…”
Section: Gdf11 Was a Target Of Mir-192mentioning
confidence: 99%
“…HFLSs participate in the development and progression of RA by producing cytokines and proteases that contribute to cartilage destruction (18). Apoptosis of HFLSs is currently considered as a potential therapeutic target for RA (19,20). Our study observed that IL-17 inhibited HFLSs apoptosis, while lncRNA CASC2 promoted HFLSs apoptosis by inhibiting IL-17.…”
Section: Discussionmentioning
confidence: 57%